A simple model of Persian reading. Issue 1 (2nd January 2016) - Sadeghi, Amir; Everatt, John; McNeill, Brigid
Abstract : This study investigated potential cognitive-linguistic predictors of reading comprehension levels of monolingual Persian-speaking children. Investigations into the Persian orthography are important since features of the orthography, such as the need to use text context to support decoding early in reading acquisition, may lead to skills developing differently from those predicted by current models of reading derived from English. Children ( N = 199) in Iranian primary schools, Grades 2 to 5 (aged between 89 and 136 months), were given measures of text reading involving (1) cloze completion and (2) passages followed by comprehension questions. Performance on these measures was analysed in relation to children's language competence, phonological ability, orthographic processing and speed of processing. Analyses indicated that Persian reading comprehension levels were predicted by measures of language-related skills and decoding ability, with the latter being predicted by phonological and orthographic processing skills. The findings were consistent with the simple view of reading being applicable to Persian despite its varying transparency between letters and sounds, though modified to take account of specific associations between orthographic knowledge and reading comprehension. A working model of Persian reading comprehension is discussed based on these findings.